Faktor-Faktor yang Berhubungan dengan Tingkat Kemandirian Anak Sekolah dalam Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) - Aprilia, Miranti; Yanuarti, Riska; Afriyanto; Angraini, Wulan (Jurnal Kesmas Asclepius, 2025)
The purpose of this study was to determine the factors related to the level of independence of elementary school children in implementing clean and healthy living behaviors at MI Nururl Huda, Bengkulu City. This research method used is a descriptive analytical study design with a cross-sectional approach and is included in the type of quantitative research, the population in this study was 35 respondents of grade 2 students at MI Nurul Huda, Bengkulu City. The results of this study are univariate results obtained by students with good independence 30 respondents (85.7), students with good knowledge 30 respondents (85.7%), the unavailability of trash cans that meet the requirements 23 respondents (65.7%). The results of the bivariate analysis showed that there was no relationship between the level of independence and the level of knowledge (p-value = 0.139), and there was a relationship between attitudes and independence (p-value = 0.49), and there was no relationship between the availability of trash cans and student independence (p-value = 0.100). In the implementation of PHBS at MI Nurul Huda, Bengkulu City. The conclusion shows that there is a relationship between attitudes and the independence of school children in the implementation of PHBS at MI Nurul Huda, Bengkulu City.  Keywords: Attitude, Elementary School, Healthy Life Behavior, Independence, Knowledge.